2020
DOI: 10.48550/arxiv.2012.12839
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cohorting to isolate asymptomatic spreaders: An agent-based simulation study on the Mumbai Suburban Railway

Alok Talekar,
Sharad Shriram,
Nidhin Vaidhiyan
et al.

Abstract: The Mumbai Suburban Railways, locals, are a key transit infrastructure of the city and is crucial for resuming normal economic activity. Due to high density during transit, the potential risk of disease transmission is high, and the government has taken a wait and see approach to resume normal operations. To reduce disease transmission, policymakers can enforce reduced crowding and mandate wearing of masks. Cohorting -forming groups of travelers that always travel together, is an additional policy to reduce di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…To demonstrate the dynamics of the spread through interactions, 158 papers simulated the disease transmission via regular or modified SIR‐ or SEIR‐based ABMs, where the labelled states of individuals are Susceptible, Infected, Recovered, Dead (SIRD) (Alsaeed et al, 2020 ; Mahmood et al, 2020 ) or Susceptible, Exposed, Infected, Recovered, Dead (SEIRD) (Benneyan et al, 2021 ; Gharakhanlou & Hooshangi, 2020 ). Some papers also introduced more COVID‐19 states, such as asymptomatic (Almagor & Picascia, 2020 ; Head et al, 2021 ; Koehler et al, 2021 ; Moghadas et al, 2021 ; Talekar et al, 2020 ), mild and severe symptoms (Alagoz et al, 2020 ; Zhang, Vilches, et al, 2020 ) and hospitalized (Nguyen et al, 2021 ; Palomo‐Briones et al, 2021 ; Son & RISEWIDs Team, 2020 ; Tadić & Melnik, 2020 ; Xu et al, 2021 ). In addition, spread through contaminated surfaces and objects (Tadić & Melnik, 2020 ) and loss of immunity (Alsaeed et al, 2020 ) were also simulated.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To demonstrate the dynamics of the spread through interactions, 158 papers simulated the disease transmission via regular or modified SIR‐ or SEIR‐based ABMs, where the labelled states of individuals are Susceptible, Infected, Recovered, Dead (SIRD) (Alsaeed et al, 2020 ; Mahmood et al, 2020 ) or Susceptible, Exposed, Infected, Recovered, Dead (SEIRD) (Benneyan et al, 2021 ; Gharakhanlou & Hooshangi, 2020 ). Some papers also introduced more COVID‐19 states, such as asymptomatic (Almagor & Picascia, 2020 ; Head et al, 2021 ; Koehler et al, 2021 ; Moghadas et al, 2021 ; Talekar et al, 2020 ), mild and severe symptoms (Alagoz et al, 2020 ; Zhang, Vilches, et al, 2020 ) and hospitalized (Nguyen et al, 2021 ; Palomo‐Briones et al, 2021 ; Son & RISEWIDs Team, 2020 ; Tadić & Melnik, 2020 ; Xu et al, 2021 ). In addition, spread through contaminated surfaces and objects (Tadić & Melnik, 2020 ) and loss of immunity (Alsaeed et al, 2020 ) were also simulated.…”
Section: Resultsmentioning
confidence: 99%
“…This review identified under‐served research areas. Only one paper simulated the transmission of COVID‐19 via suburban railways (Talekar et al, 2020 ). With the availability of big data from air transportation, highway/railway network and public transit, spatial ABMs can be built based on mobility patterns of travellers or urban populations to simulate the transmission of COVID‐19 (or other emerging infectious diseases) via intra‐ or inter‐city transport network.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation